[Poster] Exploiting high-resolution ADS-B data for flight operation reconstruction towards environmental impact assessment - Pretto, Marco; Dorbolò, Lorenzo; Giannattasio, Pietro (Journal of Open Aviation Science, 2023)
The estimation of the detrimental impact of civil air traffic on the near-airport environment is conducted by means of dedicated assessment tools, usually based on best-practice methods. However, their application involves availability of information on the flight operations, and, although the use of flight tracking data is very helpful, their full inclusion into these tools is challenging. In this paper, following the authors’ previous efforts and with the purpose of future implementation into assessment tools, highly time-resolved datasets from the OpenSky Network are used for the identification of daily flight operations. Then, the ground track reconstruction is carried out with a newly developed algorithm, which exploits the high time resolution to generate smooth trajectories using only segments and circular arcs while maintaining high accuracy, as shown in the results. This work lays the foundation for immediate future developments involving the reconstruction of aircraft performance and the estimation of airport noise levels.